Unlocking the jaw: sternoclavicular graft in temporomandibular joint ankylosis treatment - Burman, Subhasish; Das, Asish K.; Ghosh, Moumita; Khatua, Abhishek; Mukhopadhyay, Kuldip; Barman, Purbalee; Samanta, Swagatam (International Journal of Research in Medical Sciences, 2026)
Temporomandibular joint (TMJ) ankylosis is a condition that leads to impaired jaw function and growth retardation. The primary goals of treatment are to enhance mouth opening, restore joint mobility, stimulate mandibular growth, improve facial esthetics, and prevent recurrence of ankylosis. Sternoclavicualar graft is an ideal choice for reconstructing temporomandibular joint as it is similar to TMJ developmentally and structurally. We reported a case of unilateral TMJ ankylosis in an 11-year-old patient who was treated in our institute using sternoclavicular joint graft for reconstruction of ramus-condyle unit.